Pengaruh Orientasi Pasar Dan Inovasi Produk Terhadap Kinerja Pemasaran Saat Pandemi Covid-19 (Studi Kasus Pada Kelompok Usaha Bersama Jati Aji di desa Geneng Kecamatan Margomulyo Kabupaten Bojonegoro)” - Jayanto Tri Shac Seno; N. Rachma; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract From export data obtained from data from the Ministry of Industry's Center for Data and Information in 2020, it is stated that during the Covid-19 pandemic, changes in furniture exports in East Java were very unstable. Furniture export activities also affect the business group with the Jati Aji, because most of the buyers from this group flee their merchandise abroad. The reason for this is to take a look at turned into to decide the impact of marketplace orientation and product innovation on marketing performance during the covid-19 pandemic (Case Study of the Jati Aji Joint Business Group in Geneng Village, Margomulyo District, Bojonegoro Regency. The population of this study were members of the Jati Aji Joint Business Group. In this study using a saturated sample technique. So the number of samples used in this study were 55 members of the Jati Aji Joint Business Group. The results of the study show that the opinion of business actors on the market orientation carried out is that understanding and being good with customers and monitoring the strengths of competitors is something that must be done. From the results of product innovation which states that it has no significant effect on marketing performance, it can be explained that product innovation is carried out by members of the joint business group. Keywords: Market Orientation, Product Innovation, Marketing Performance, Jati Aji Joint Business Group.